Peran Permainan Interaktif dalam Pengembangan Bahasa Anak Usia Dini - Nurul Fadilah; Syamsiah Depalina (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the role of interactive play in early childhood language development in Sipolu-polu Village, Panyabungan District. Interactive games are a fun and educational approach that supports children's language skills, particularly vocabulary acquisition, sentence structure, storytelling ability, and two-way communication. This research employed a qualitative descriptive method using observation, interviews, and documentation techniques. The subjects were children aged 4–6 years involved in interactive play activities within non-formal education settings and their home environments. The findings show that interactive games, such as role-playing, picture puzzles, and educational digital games, have a positive impact on children's language development. Children became more verbally active, followed instructions better, and could express ideas and stories in a more structured manner. Therefore, interactive games are proven to play a significant role as an effective learning medium in developing early childhood language skills in the community of Sipolu-polu Village.